Assessment of brain two-dimensional metrics in infants born preterm at term equivalent age: Correlation of ultrasound scans with magnetic resonance imaging - Vo Van, Philippe; Beck, Jonathan; Meunier, Hélène; Venot, Perrine; Mac Caby, Gratiella; Bednarek, Nathalie; Loron, Gauthier (Frontiers in Pediatrics, 2022)
Context Developing brain imaging is a critical subject for infants born preterm. Impaired brain growth is correlated with poor neurological outcomes, regardless of overt brain lesions such as hemorrhage or leukomalacia. As Magnetic Resonance Imaging (MRI) remains a research tool for assessing regional brain volumes, two-dimensional metrics (2D-metrics) provide a reliable estimation of brain structures. In neonatal intensive care, cerebral UltraSound (cUS) is routinely performed to assess brain integrity. This prospective work has compared ultrasound and MRI accuracy for measurement of 2D brain metrics and identification of overt injuries. Methods MRI and cUS were performed at term equivalent age (TEA) in infants born before 32 Weeks of Gestation (GW). Demographical data and results of serial cUS (NICU-US) performed during hospitalization were gathered from medical charts. Blinded, experienced senior doctors reviewed the scans for both standard analysis and standardized, 2D measurements. Correlation of 2D metrics and Inter/Intra observer agreements were evaluated using Pearson's coefficient, Bland-Altman plots and Intra Class Coefficient, respectively. Results One hundred and two infants born preterm were included. The performance of “TEA-cUS and NICU-cUS” compared to “TEA-MRI and NICU-cUS” was identical for the detection of high-grade haemorrhages, and close for low-grade ones. However, TEA-MRI only detected nodular lesions of the white matter. No infant presented a cerebellar infarct on imaging. Intra and inter-observer agreements were excellent for all 2D metrics except for the corpus callosum width and anteroposterior vermis diameter. MRI and cUS showed good to excellent correlation for brain and bones biparietal diameters, corpus callosum length, trans cerebellar and lateral ventricles diameters. Measures of corpus callosum width and vermis dimensions were poorly correlated. Conclusion and perspective Cerebral US is to be a reliable tool to assess selected 2D measurements in the developing brain. Repetition of these measurements on cUS repeted during NICU stay would allow the completion of growth charts for several brain structures. Further studies will assess whether these charts are relevant markers of neurological outcome.